Concert at the Margravial Opera House - Africa Multiple Cluster of Excellence (Conference 2019, 2019)
On 30 October 2019, four musicians came together at the festive Margravial Opera House in Bayreuth to perform as part of the kick-off event of the Africa Multiple Cluster of Excellence. Tomas Childo, Tao Ravao, EunKyung Kim, Jae-Hyo Chang and Matchume Chango had rehearsed for only one week to present that spectacular and once in a lifetime concert.